Perancangan Aplikasi Rekap Data dan Operation Maintenance Pada Perusahaan Iforte - Zalzabila Syafa Nurul Arsy; Muhamad Bahrul Ulum (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2023)
By developing an application for processing TT (Trouble Ticket) report data, it becomes possible to streamline the tasks of employees involved in handling TT reports and generating corresponding reports. This web-based software has been designed using the PHP programming language and relies on a MySQL database. The primary objective of implementing this web solution is to enhance the archiving process and serve as an efficient replacement for less effective and inefficient methods, ultimately simplifying the creation of TT (Trouble Ticket) data reports. In essence, the application is designed to improve the workflow and efficiency for employees dealing with TT reports. It leverages web technology to optimize the archiving process and reporting, making the entire TT data management process more streamlined and effective.